Частота мікроальбумінурії у хворих на гіпотиреоз - Дідушко, О. М. (Clinical Endocrinology and Endocrine Surgery, 2012)
The purpose of research – the study of the frequency and magnitude of microalbuminuria (MAU) in patients with primary hypothyroidism, the establishment of the degree of relationship of microalbuminuria with major risk factors. Under supervision were 58 patients (12 men and 46 women) with primary hypothyroidism. The frequency of microalbuminuria in patients with hypothyroidism reaches 46.6%, depending on the duration of the disease, being in the range of 16.7% to 57.6%. Likelihood of microalbuminuria increases with systolic and diastolic blood pressure. There was a significant correlation between the level of blood pressure and pulse rate of microalbuminuria detection (p = 0.045). The prevalence of microalbuminuria in patients with hypothyroidism increases with the presence of diastolic dysfunction of the left ventricle. Correlation relationship MAU values and indicators of thyroid function, and lipid profile in patients with hypothyroidism is not established.